Company size and differences in injury prevalence among apprentices in building and construction in Norway. (January 2015) - Holte, Kari Anne; Kjestveit, Kari; Lipscomb, Hester J.
Highlights: In construction there is increased injury risk for apprentices in small companies (<50 employees). Risk-factors likely differ due to differences in trade and size-specific differences in exposure. Apprentices in the electrical trade were at greatest risk in companies with 10–19 employees. Apprentices in building were at greatest risk in companies with 20–49 employees. Apprentices in microbusinesses seem not to be at particularly high risk of injury. Abstract: An increased risk for injuries is found in small enterprises, and is especially evident for the construction industry. Our aim was to study injury risk among apprentices in different sized enterprises within different building and construction trades. The study design was a cross-sectional survey among all apprentices in a county in Western Norway, designed to assess injury involvement during the apprenticeship period. Six-hundred seventy-three ( n = 673) apprentices completed the questionnaire, giving a response rate of 81%. Overall the prevalence of injuries was higher among apprentices in training companies with 10–19 employees. However, trade-specific analysis for apprentices in building and electrical trades showed different patterns regarding injury risk across different company sizes, with increased risk in companies with 10–19 employees for the electrical trade and in companies with 20–49 employees in the building trade. In conclusion, when considering injury risk among young workers, nature of work and associated exposures, as well as other characteristics that may vary by size of the enterprise, should be assessed.